Cellulitis Caused by a Novel Cupriavidus Species Strain J1218 Identified by Whole Genome Sequencing - Ko, Young Jin; Yoon, Soo-Young; Lim, Chae Seung; Lee, Chang Kyu (Annals of clinical microbiology, 2019)
We report a case of cellulitis caused by a novel Cupriavidus species identified using whole-genome sequence analysis. Subcutaneous tissue biopsies from the left lower leg of a 67-year-old man who suffered from cellulitis were cultured. Round, convex, gray and non-hemolytic colonies were recovered after 72-h incubation. 16S rRNA sequence analysis showed 98.6% similarity with Cupriavidus basilensis DSM 11853(T) in the NCBI database and 99.9% similarity with C. basilensis KF708 in the EzBioCloud database. Genomic analysis using the MiSeq platform (Illumina, USA) and the TrueBac ID database (ChunLab, Korea) revealed that the average nucleotide identity (ANI) of this strain with C. basilensis DSM 11853(T) was 87.6%. The patient was treated with oral cefditoren pivoxil for 9 weeks. This study is the first to report cellulitis caused by Cupriavidus species strain J1218. (Ann Clin Microbiol 2019;22:105 -109)